Library management in Spain (2005-2010): trends and significant changes - Pacios Lozano, Ana Reyes (Revista General de Información y Documentación, 2012)
An overview of the management trends in relation to Spanish libraries during the last five years is offered. The most significant issues identified have repercussions on the implementation of management techniques and on the management of library resources (collection, human resources, spaces, and equipment), showing some significant changes. Examination and analysis of the works published during that period in journals, and of proceedings of congresses, conferences and seminars, essentially, as well as the developments of working groups created within different professional associations, unveil the fundamental lines of interest. These are the lines on which professionals and teachers devoted to management have focused over that period, contributing experiences, reflections and solutions.